Resurgence of Violence in Southern Thailand: The Role of Domestic Factors (Journal of International Studies, 2020)
The southernmost provinces of Pattani, Yala and Narathiwat, otherwise known as changwat chaidaen pak tai (southern border provinces), where most of the currentviolence is taking place, proves to be the hardest region for the Thai government tointegrate with Bangkok. These provinces have also experienced endless turmoil sincethey were brought under Bangkok's rule. These resistance movements have taken placeparticularly between the years of 1950s up to 1980s, but in the last decade, have lostmuch of their momentum as a result of improved diplomatic and economic relationswith the central government of Bangkok. However, the beginning of the twenty-firstcentury again witnessed a recurrence or resurgence of similar uprisings. Why has theconflict reappeared? This paper attempts to understand the causes leading to theresurgence of the conflicts despite its waning in the 1980s and 1990s. The paper willfocus in particular on the domestic factors "enabling" the conflict by referring to someof the recent events that have taken place in southern Thailand. The paper argues that the violence in the south is very much attributed to the government's policy, especially the issue of its heavy-handed strategy and in turn, the paper will demonstrate the positive correlation between persecution and violence. The term persecution in this paper is, however, confined to the government's heavy handed strategy that is reflected mainly by operations carried out by the security forces.